Pengaruh Komitmen Organisasi dan Stres Kerja terhadap Turnover Intention Karyawan di PT BPRS HIK Parahyangan Bandung - Ayu Fuji Lestari; Yasir Muharram Fauzi; Adi Indradi Wazdi (Ma'soem University, 2021)
Based on the results of the initial research, that the background of this research is the fluctuating Turnover Intention data at PT BPRS HIK Parahyangan Bandung.This study aims to determine how the influence of Organizational Commitment on Employee Turnover Intention at PT BPRS HIK Parahyangan Bandung, to find out how the effect of Work Stress on Employee Turnover Intention at PT BPRS HIK Parahyangan Bandung, and to find out how the influence of Organizational Commitment and Work Stress simultaneously on Turnover Intention Employees of PT BPRS HIK Parahyangan Bandung. The object of research in this report is to determine the effect of Organizational Commitment and Work Stress on Turnover Intention at PT BPRS HIK Parahyangan Bandung. The type of research is quantitative associative, the type of data is primary data and uses data collection techniques in the form of observations, interviews, literature studies and questionnaires. While the sampling technique is probability sampling with a total of 71 populations and 60 samples. The results showed that there was an influence between Organizational Commitment (X1) partially significant effect on Employee Turnover Intention (Y) at PT BPRS HIK Parahyangan Bandung, this can be seen in the t test, namely tcount 6,035 > ttable 2,002. There is the influence of Work Stress (X2) at PT BPRS HIK Parahyangan Bandung partially significant effect on Employee Turnover Intention (Y) at PT BPRS HIK Parahyangan Bandung this can be seen in the t test, namely tcount 6,290 > tcount 2,002, and simultaneously Organizational Commitment ( X1) and Work Stress (X2) have a significant effect on Employee Turnover Intention (Y) at PT BPRS HIK Parahyangan Bandung. This can be seen in the results of the F test, namely Fcount 22.856 > Ftable 3.16.